Aspects of care culture in municipal care for elderly people: a hermeneutic documentary analysis of reports of abuse. Issue 2 (31st July 2012) - Rytterström, Patrik; Arman, Maria; Unosson, Mitra
<x xml:space="preserve">Abstract</x> Scand J Caring Sci; 2013; 27; 354–362 Aspects of care culture in municipal care for elderly people: a hermeneutic documentary analysis of reports of abuse Introduction: Care culture is an important contextual factor in care practice. Care culture refers to a process of creating meaning out of tradition, horizon and bildung. The care culture is often taken into consideration in situations that go beyond the everyday routine, such as cases of abuse. In Sweden, health care professionals are obliged to document and report any suspected bad conditions. Although the reports have the potential to communicate underlying values and assumptions about the care culture, such studies have not been performed. Aim: The aim of this study was to understand how elderly care abuse in institutions could be understood from a care culture perspective. Design and methods: A hermeneutic documentary analysis was conducted on 269 incident reports concerning suspected mistreatment of the elderly in three municipalities in Sweden. The hermeneutic analysis followed a four‐stage process: selecting and reading the text, setting out the context, closing the hermeneutic circle, and finally creating a conceptual bridge towards a critical understanding from a phenomenological lifeworld perspective. Findings: The care of the elderly in the municipality was based on a social culture that placed residents' needs at the centre. Following routines were considered important in preventing mistreatment and were intended to ensure that all patients were treated fairly and equally. Care was described as task oriented and often lacking in interpersonal relations. From a phenomenological lifeworld perspective, it was interpreted that in the municipalities' care of the elderly, there was a focus on elderly people's freedom at the expense of the vulnerability aspects of well‐being. Conclusion: Raising awareness of the care culture underlying abuse could help to improve understanding of care practice. Change may be only possible when reflected on the existing perspectives underpinning the care culture, and integrate them into a broader framework for caring.